The Spirit of romanticism [videorecording] - Barnes, John.; Encyclopedia Britannica Educational Corporation (Chicago, Il.). (Chicago Encyclopedia Britannica Educational Corporation [producer], 1977)
Outlines the historical events and cultural influences of the Romantic age, using vignettes which highlights the causes of such figure as Jean Jacques Rosseau ; Napoleon Bonaparte, Carlyle, Wordsworth, Sheley, Byron, Beethoven, Delacroix, and Chopin.
VHS.
Keywords: Romanticism; Arts, Modern -- 19th century; Nineteenth century; Romanticism in art